2010
DOI: 10.1007/s10549-010-0870-7
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of interest in economic analyses of aromatase inhibitors in breast cancer: a systematic review

Abstract: To determine whether authors conducting economic analyses of aromatase inhibitors in breast cancer are less likely to reach unfavorable conclusions if the economic study is sponsored by the manufacturer of the drug. Articles reporting the economic analyses of aromatase inhibitors in breast cancer were selected from PubMed in May 2009. Information was collected on the types of analysis, the qualitative conclusion, the quantitative results, and the funding sources. Fisher's exact test was conducted to compare th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…These outcomes confirm the conclusions made by Jang et al [51] that economic evaluations funded by a pharmaceutical company are less likely to reach unfavorable conclusions, but it must be kept in mind that in this case it only occurred in two analyses and that nonpharmaceutical companysponsored studies also calculated high ICERs.…”
Section: Nosupporting
confidence: 87%
“…These outcomes confirm the conclusions made by Jang et al [51] that economic evaluations funded by a pharmaceutical company are less likely to reach unfavorable conclusions, but it must be kept in mind that in this case it only occurred in two analyses and that nonpharmaceutical companysponsored studies also calculated high ICERs.…”
Section: Nosupporting
confidence: 87%
“…Compared to other systematic reviews we employ no language restrictions. [51], [52] We also systematically assess important potential sources of bias in CEA. Our analysis also compares predictions of model-based CEAs for AIs to clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al demonstrated that industry sponsored CEAs were significantly more likely than CEAs conducted by independent academic centres to reach favourable conclusions about the cost-effectiveness of AIs. [52] It was beyond the scope of our analysis to quantify the impact of industry sponsorship on methodological choices and CEA conclusions, even though association between industry-sponsorship and favourable CEA findings is well established. [62][64] We focused only on AIs in the first-line setting, and thus had limited statistical power to detect differences.…”
Section: Discussionmentioning
confidence: 99%
“…8 Their more favourable results are obtained mostly by comparing the industry-sponsored medication against inferior comparators (e.g., placebo or a "straw-man" medication with little or no effectiveness). 8 Similarly, several studies suggest that company-sponsored cost-effectiveness analyses are more likely to report favourable qualitative conclusions [9][10][11][12][13] and one systematic review concluded that such studies reported favourable incremental cost-effectiveness ratios 1 compared with nonsponsored studies. For example, in an empirical evaluation of 495 cost-effectiveness analyses, industry sponsorship increased threefold the odds of an incremental cost-effectiveness ratio below $50 000 per quality-adjusted life year.…”
Section: Discussionmentioning
confidence: 99%